2020
DOI: 10.1103/physrevb.102.054430
|View full text |Cite
|
Sign up to set email alerts
|

Orbital selective spin waves in detwinned NaFeAs

Abstract: This is a copy of the published version, or version of record, available on the publisher's website. This version does not track changes, errata, or withdrawals on the publisher's site.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…As demonstrated using INS [83] and other techniques [84], it should be possible to detwin NaFeAs (or other parent compounds of FeSCs) by applying a small strain in RIXS experiments. For NaFe 0.53 Cu 0.47 As, as twinning is due to Fe-Cu ordering already present at room temperature, it is unlikely strain will have a similar detwinning effect.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated using INS [83] and other techniques [84], it should be possible to detwin NaFeAs (or other parent compounds of FeSCs) by applying a small strain in RIXS experiments. For NaFe 0.53 Cu 0.47 As, as twinning is due to Fe-Cu ordering already present at room temperature, it is unlikely strain will have a similar detwinning effect.…”
Section: Discussionmentioning
confidence: 99%
“…From both the nuclear magnetic resonance and neutron scattering measurements, coexistence of both itinerant and local spins has been found 17 , where the d xy orbital contributes dominantly to the local spin susceptibility [18][19][20] . As an example, inelastic neutron scattering experiments on detwinned NaFeAs, a parent compound of FeSCs, have shown that spin waves of the system are orbital-selective with high energy spin waves arising mostly from the d xy orbital and obeying the C 4 rotational symmetry, while the low energy spin waves are from the d xz /d yz orbitals that break the C 4 rotational symmetry below the nematic phase transition temperature 21,22 .…”
mentioning
confidence: 99%
“…After that, the crystals were cut into rectangle shapes (typical sizes: 1 mm × 2 mm) by a wire saw under the directions [1, 0, 0] × [0, 1, 0] in orthorhombic lattice notation (a = b = 5.6 Å). By applying a uniaxial pressure around 10 MPa, the crystal can be fully detwinned at low temperature, where the direction of pressure was defined as b direction, and the pressure-free direction was defined as a direction [60][61][62][63][96][97][98][99] . The in-plane resistivity (ρ a,b ) was measured by the standard four-probe method with the Physical Property Measurement System (PPMS) from Quantum Design.…”
Section: Experiments Detailsmentioning
confidence: 99%